2019
DOI: 10.1093/ajcp/aqz006
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Milan System for Reporting Salivary Gland Cytopathology: A Retrospective 12-Year Bi-institutional Study

Abstract: Objectives Multi-institutional studies are required for the validation of the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC). Methods A total of 1,560 fine-needle aspirations of the salivary glands were retrieved from two institutions for a 12-year period. The diagnoses were reclassified based on the MSRSGC. Risk of malignancy (ROM) for each category was calculated based on 694 histologic follow-up cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
86
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(118 citation statements)
references
References 16 publications
26
86
3
Order By: Relevance
“…The ROM rates for the other categories were broadly in line with those suggested in the MSRSGC. Overall, the ROM rates obtained in our institution were within previously reported ranges for all diagnostic categories (Table ) …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The ROM rates for the other categories were broadly in line with those suggested in the MSRSGC. Overall, the ROM rates obtained in our institution were within previously reported ranges for all diagnostic categories (Table ) …”
Section: Discussionsupporting
confidence: 93%
“…In the studies of Rossi et al, Viswanathan et al, and Wu et al, lymphoma was the main cause of false negative results with classification in the nonneoplastic category, whereas Rohilla et al reported that the ROM of the nonneoplastic category was ascribed to mammary analog secretory carcinoma, mucoepidermoid carcinoma, and carcinoma ex pleomorphic adenoma. In our study, the six specimens in the benign neoplasm category were found to be carcinoma ex pleomorphic adenoma (n = 5) or MALT lymphoma (n = 1) at the surgical follow‐up, which is similar to the observations of Viswasnathan et al and Wu et al, who found that most false negative cases in the benign neoplasm category were carcinoma ex pleomorphic adenoma (8/16). Rohilla et al reported three cases of false negative diagnoses in the benign neoplasm category, including mucoepidermoid carcinoma (n = 2) and oncocytic carcinoma (n = 1), while in the study by Rossi et al, there were 28 false negative diagnoses in which mucoepidermoid carcinoma (7/28, 25%) comprised the majority of the results.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations